Implementasi Kewajiban Perpajakan Orang Pribadi Dari Penghasilan Multi Profesi - Sunarmin -- Sunarmin (Jurnal Pajak Vokasi (JUPASI), 2022)
One of the main objectives of making this Final Project Report is to find out whether the Implementation of Calculation, Depositing and Reporting of Annual Personal Tax Return on Income Originating from Mr. X's Multi Profession in 2019. And to achieve that goal, the writer has observed and cited documents. From the observations made by the author, it can be concluded that the Implementation of Calculation, Depositing and Reporting of Annual Annual Personal Tax Returns Income originating fromMr. X's Multi Profession in 2019 is not in accordance with the provisions ofthe Law and Regulation of the Minister of Finance. Because it is not appropriate, the authors suggest that Mr. X do the Correction 1 tax returnfor the mistakes and problems faced by Mr. X in his taxation obligations.